Postdiction: its implications on visual awareness, hindsight, and sense of agency - Shimojo, Shinsuke (Frontiers in Psychology, 2014)
There are a few postdictive perceptual phenomena known, in which a stimulus presented later seems to causally affect percept of another stimulus presented earlier. While backward masking provides a classical example, the flash lag effect stimulates theorists with a variety of intriguing findings, and the TMS-triggered scotoma and its filling-in offer a unique neuroscientific case. Findings suggest that various visual attributes are reorganized in a postdictive fashion to be consistent with each other, or to be consistent in a causality framework. In terms of underlying mechanisms, three prototypical models have been considered: the “catch up,” the “reentry” and the “different pathway” models. By extending the list of postdictive phenomena to memory, sensory-motor and higher-level cognition, one may note that such postdictive reconstruction may be a general principle of neural computation, ranged from milliseconds to months of time scale, from local neuronal interactions to long-range connectivity, in the complex brain. It has significant implications in interpreting “free will” and “sense of agency” in functional, psychophysical and neuroscientific terms.